2019
DOI: 10.1038/s41598-019-44605-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased sea ice cover alters food web structure in East Antarctica

Abstract: In recent years, sea ice cover along coasts of East Antarctica has tended to increase. To understand ecological implications of these environmental changes, we studied benthic food web structure on the coasts of Adélie Land during an event of unusually high sea ice cover (i.e. two successive austral summers without seasonal breakup). We used integrative trophic markers (stable isotope ratios of carbon, nitrogen and sulfur) to build ecological models and explored feeding habits of macroinvertebrates. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 59 publications
(80 reference statements)
4
44
1
Order By: Relevance
“…Although global warming is associated with decreases in arctic sea ice, there is regional variability in the Antarctic with reductions in the west but increasing sea ice cover in the Ross Sea and East Antarctica (Parkinson and Cavalieri ). Such changes could have major implications for food webs (Norkko et al , Michel et al ) and foraging conditions along the East Antarctic coastline. Polar regions are sensitive to climate change (Goosse et al ), but the complexity of geophysical processes in the Antarctic, particularly multidecadal‐scale contributions by deep‐water convection currents in the Southern Ocean (Zhang et al ) currently limits the ability to predict how the extent of Antarctic sea ice will be affected by anthropogenic climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Although global warming is associated with decreases in arctic sea ice, there is regional variability in the Antarctic with reductions in the west but increasing sea ice cover in the Ross Sea and East Antarctica (Parkinson and Cavalieri ). Such changes could have major implications for food webs (Norkko et al , Michel et al ) and foraging conditions along the East Antarctic coastline. Polar regions are sensitive to climate change (Goosse et al ), but the complexity of geophysical processes in the Antarctic, particularly multidecadal‐scale contributions by deep‐water convection currents in the Southern Ocean (Zhang et al ) currently limits the ability to predict how the extent of Antarctic sea ice will be affected by anthropogenic climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Wlodarska-Kowalczuk et al (2004) showed, for example, that areas characterized by seasonal ice coverage had higher abundances of the benthic macrofauna compared to areas characterized by perennial ice coverage. Moreover, the lack of sea ice break-up events strongly alters the benthic food-web structure, causing a shift on the diet of the benthic organisms (Michel et al, 2019).…”
Section: Ice Coverage and Chlorophyll-a Concentrationmentioning
confidence: 99%
“…Specifically, sea-ice shrinking during spring, together with sea-ice break-up in summer, allows a massive increase in ice-bound primary production (sympagic production), which is subsequently released into the water column, fuelling both pelagic and benthic communities (Pusceddu et al, 1999;Lizotte, 2001;Leu et al, 2015). Under these conditions, sympagic algae represent the main direct (via vertical flux) and indirect (after sedimentation) food input for a large part of Antarctic marine diversity (Lizotte, 2001;Michel et al, 2019;Rossi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The increased availability of basal resources after sea-ice break-up allows consumers to exploit a range of carbon sources in both the water column and on the bottom, reinforcing benthic-pelagic coupling (Cattaneo-Vietti et al, 1999;Kaehler et al, 2000;Dunton, 2001;Knox, 2006). The seasonal supply of sympagic algae thus becomes crucial to energy exchanges between ecosystem compartments, also affecting the structure and stability of communities (Hobson et al, 1995;Søreide et al, 2010;Leu et al, 2015;McMeans et al, 2015;Michel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation